Intracellular K+-Responsive Block Copolymer Micelles for Targeted Drug Delivery of Curcumin - Jiang, Mingyue; Chen, Le; Chen, Bo; Yu, Qinghua; Zhang, Xianming; Jing, Weihong; Ma, Limei; Deng, Tao; Yang, Zhangyou; Yu, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Curcumin (CUR) is a natural bioactive compound that has come to attention as a “golden molecule” due to its therapeutic properties against several types of tumors. Nonetheless, the antitumor application of CUR is hampered due to its extremely low aqueous solubility and chemical instability. Herein, a novel type of polymeric micelles encapsulating CUR with intracellular K+-responsive drug-release properties is designed and developed. The polymeric micelles are self-assembled by poly(N-isopropylacrylamide-co-acryloylamidobenzo-15-crown-5-co-N,N-Dimethylacrylamide)-b-DSPE (PNDB-b-DSPE) block copolymers and CUR. CUR is successfully loaded into the micelles with CUR loading content of 6.26 wt%. The proposed CUR-PNDB-DSPE polymeric micelles exhibit a significant CUR release in simulated extracellular fluid due to the formation of 2 : 1 ‘‘sandwich’’ host-guest complexes of 15-crown-5 and K+, which lead to the hydrophilic outer shell collapses and the drug rapidly migrate out of the micelles. In vitro cell experiments indicate that CUR-PNDB-DSPE micelles exhibit a high cellular uptake and excellent intracellular drug release in response to the intracellular K+ concentration of B16F10 cells. Moreover, CUR-PNDB-DSPE micelles show a high cytotoxicity to B16F10 cells compared to free CUR and CUR-PEG-DSPE micelles. The polymeric micelles with intracellular K+-responsive drug release properties proposed in this study provide a new strategy for designing novel targeted drug delivery systems for CUR delivery for cancer treatment.